Jus Wortel Dapat Menurunkan Hipertensi Pada Ibu Hamil : Literatur Review - Katili, Dwi Nur Octaviani; Mulyaningsih, Sri; Wirono, Maryani Eka (Indonesia Berdaya, 2024)
Hypertension in pregnancy is is hypertension that occurs during pregnancy and usually in the last month of pregnancy or more after 20 weeks of gestation in women who were previously normotensive, blood pressure values 120/80 mmHg, or an increase in systolic pressure of 30 mmHg and diastolic pressure of 15 mmHg above the normal value. This literature study aims to identify the influence of carrot juice that decrease hypertension. The method used Literature study that was conducted by searching articles which is published on Google Scholar, IOS, and Garuda Portal. In keywords: carrot juice can reduce hypertension in pregnant women. Searching the literature was published in the last 10 years from 2009 to 2019 with full text in Indonesian language relevant to the topic of research. The results based in a review on 5 articles, it was found that carrot juice had an influence on maternal blood pressure where there are differences in pressure values before and after being given carrot juice itself. Based on the research results, it can be concluded that carrot juice is an alternative non-pharmacological treatment for hypertension.